A Portrayal of the Main Characters' Change of Persistence in Little Women and Little Men by Louisa May Alcott - Indah Amanda Maharani; Sri Sumaryani (Rainbow: Journal of Literature, Linguistics and Culture Studies, 2025)
The Victorian era had a profound impact on the lives of women during that period. However, with the persistence in achieving dreams, the norm was slightly broken. Persistence is a characteristic that shows one's behavior to maintain perseverance and enthusiasm in achieving goals. The character of persistence is marked by a strong and tireless consistency in the effort to achieve something. Little Women portrays the persistence of the main character, who lives in the Victorian era. This study aims to describe the persistence of the main character in the novel Little Women, who finally broke her word and chose a new path in life in the novel Little Men. The method used is qualitative research using Sigmund Freud's psychoanalysis theory. In this study, Jo shows persistence in achieving her dreams and succeeding, but the environment and ego continue to develop so that Jo begins to break her own words.